2022
DOI: 10.3390/biom12010105
|View full text |Cite
|
Sign up to set email alerts
|

Liver Stiffness, Albuminuria and Chronic Kidney Disease in Patients with NAFLD: A Systematic Review and Meta-Analysis

Abstract: An association between liver stiffness, a surrogate measure of liver fibrosis, and chronic kidney disease (CKD) in patients with nonalcoholic fatty liver disease (NAFLD) has been proposed. However, most studies were small and had low statistical power. We systematically searched PubMed-MEDLINE and Scopus from inception to August 2021 for cross-sectional or cohort studies reporting the association between liver stiffness diagnosed by vibration controlled transient elastography (VCTE) and renal dysfunction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The effects on liver function, hepatocyte proliferation, liver tumors, liver immunity, and cholesterol and bile acid metabolism cannot be ignored. There is substantial evidence that impaired structure and function of liver tissues or cells can affect the function of other tissues and organs; for example, emerging changes in renal function in patients with acute or chronic liver disease often lead to acute kidney injury [ 161 ] or chronic kidney diseases [ 162 ]. Severe abnormalities in liver function can even damage the nervous system and cause central nervous system dysfunction, leading to the development of hepatic encephalopathy [ 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects on liver function, hepatocyte proliferation, liver tumors, liver immunity, and cholesterol and bile acid metabolism cannot be ignored. There is substantial evidence that impaired structure and function of liver tissues or cells can affect the function of other tissues and organs; for example, emerging changes in renal function in patients with acute or chronic liver disease often lead to acute kidney injury [ 161 ] or chronic kidney diseases [ 162 ]. Severe abnormalities in liver function can even damage the nervous system and cause central nervous system dysfunction, leading to the development of hepatic encephalopathy [ 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, GHF and NAFLD share a common pathophysiology and similar phenotype. Thanks to previous studies, it is well known that the degree of liver fibrosis is strongly associated with albuminuria and CKD in patients with NAFLD [ 32 ]. Increased IR, which is a major causative factor of NAFLD [ 33 ], has also been associated with GHF [ 13 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to previous studies, it is well known that the degree of liver fibrosis is strongly associated with albuminuria and CKD in patients with NAFLD [ 32 ]. Increased IR, which is a major causative factor of NAFLD [ 33 ], has also been associated with GHF [ 13 , 31 , 32 ]. Obesity that induces IR promotes oxidative stress along with chronic inflammation, and dysregulation of adipokines, which are secreted from subcutaneous fat or visceral fat in obese patients and contribute to the development of ectopic fat accumulation in the liver, may be associated with renal hyperfiltration [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, accumulating observational studies using vibration controlled transient elastography (VCTE), as non-invasive method to evaluate the degree of liver fibrosis, also reported an independent association between liver stiffness and renal dysfunction. In this regard, for instance, in a 2022 systematic review and meta-analysis of seven cross-sectional studies for a total of 7736 individuals with NAFLD, Ciarduillo et al showed that liver fibrosis (as assessed by VCTE) was associated with an increased risk of prevalent CKD (defined as eGFR < 60 mL/min/1.73 m 2 and urinary albumin to creatinine ratio ≥30 mg/g) (randomeffects odds ratio 2.49, 95% confidence interval 1.89-3.29; I 2 = 46.5%), as well as with an increased risk of prevalent albuminuria (random-effects odds ratio 1.98, 95% confidence interval 1.29-3.05; I 2 = 46.5%) [32]. However, it should be noted that, at present, only few observational studies on this topic have used liver biopsy for the diagnosis of NAFLD, which is the reference standard for diagnosing and staging NAFLD [1,2].…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 99%